The effect of linum usitatissimum (flax seed) and nigella sativa oil on selected oral pathogen (Comparative study) - Mohamed Yusoff, Nurul Fatihah; Mustafa Al-Ahmad, Basma Ezzat (2019)
Nowadays the people are more concerned, conscious and are more inclined to use natural products and preference change to herbal instead of synthetic medication is because of sever side effects of some materials or facing the potential risk of bacterial resistance. Bacteria and their products play an important role in the pathogenesis of polio-periapical disease. Predominant microbial groups often isolated from infected root canals are the aerobic and facultative anaerobic organisms. Linum usitatissimum (flaxseed, flax plant) Cultivated for domestic use As dietary supplement because of multitudinous effect on human health Also used to treat constipation Nigella sativa (Habbah Sawda or Habbat el Baraka) Black cumin herb Translated as seed of blessing Potent anti inflammatory, anticancer, anti infertility, anti diabetic, antimicrobial, antihistamine and anti hypertensive effects